Pengembangan Sistem Informasi Kawasan Agrowisata Menggunakan Konsep Model View Control berbasis Web - Syahrul Mubarok Nur Muhammad; Ferdi Ahmad Mauladi; Risky Kurniawan; Rangga Sanjaya (Universitas Hamzanwadi, 2022)
The business process of selling products from the Cimanggis Village community is still conventionally with a marketing strategy of offering words of mouth through business partners such as the community, retail, and markets, and the lack of access to information about product sales can hinder the product marketing process. This study aims to create a web-based agro-tourism area information system to help BUMDes and village UMKM overcome problems in ongoing business processes. Observation and interviews are methods used to collect data (needs analysis). Meanwhile, the MVC concept and the agile software development method were used to build an information system for agro-tourism areas in Cimanggis Village. This agro-tourism area information system is tested using black-box testing. The results of this study are data on UMKM activities and business processes in Cimanggis Village, design of information systems for agro-tourism areas, and evaluation of information systems. Data on business activities and processes are displayed in the current system analysis. The design of the information system is displayed in business processes, UML diagrams, and user interface views of the information system. The evaluation results show that the agro-tourism area information system can manage transaction data and information on UMKM products and tourism services with good results.